Nonviolent political economy: a research and teaching agenda (2019)
In this introductory article some of the great heresies of the heterodox economists are explained (as well as those of anthropologists, biologists, historians, political scientists, philosophers, etc.). These go beyond the narrow disciplinary frameworks (and emerge as examples of universalist thought), and thus broaden the perspectives of economic thought towards a nonviolent political economy. This broadening occurs in the following directions: a) diagnoses of conventional economic theory; b) ideas of a nonviolent political economy; c) amplified views about social conflict; d) bioeconomics and its derivatives; e) moral economy; f) the political economy of love and other non-egoistic motivations; and g) elaborated models of individual and collective choice